A new primitive Neornithischian dinosaur from the Jurassic of Patagonia with gut contents - Salgado, Leonardo (2017)
We describe a new species of an ornithischian dinosaur, Isaberrysaura mollensis gen. et sp. nov. The specimen, consisting in an almost complete skull and incomplete postcranium was collected from the marine-deltaic deposits of the Los Molles Formation (Toarcian-Bajocian), being the first reported dinosaur for this unit, one of the oldest from Neuquén Basin, and the first neornithischian dinosaur known from the Jurassic of South America. Despite showing a general stegosaurian appearance, the extensive phylogenetic analysis carried out depicts Isaberrysaura mollensis gen. et sp. nov. as a basal ornithopod, suggesting that both Thyreophora and neornithischians could have achieved significant convergent features. The specimen was preserved articulated and with some of its gut content place in the middle-posterior part of the thoracic cavity. Such stomach content was identified as seeds, most of them belonging to the Cycadales group. This finding reveals a possible and unexpected role of this ornithischian species as seed-dispersal agent.